Analisis Produktivitas Usaha Peternak Ayam Ras Pedaging Pola Kemitraan Perusahaan Pengelola Di Kecamatan Mojo Kabupaten Kediri - Pamuji Setyo Utomo; M. Darul Anwar (Manajemen Agribisnis: Jurnal Agribisnis, 2022)
The objectives of this study are to analyse the relation of input production Broiler hens, farmer experience, labor, and extension with the productivity of Patnership Farming Activities at Mojo Sub-district Kediri. This study was be done on 15 July 2021 until 31 Agustust 2021. The information and data were collected by survey on 30 respodents. The respodents were selected using purposive sampling (judgmental sampling) method. The result of this study indicated that the respondent operate with high productivity is about 6.67% ; medium productivity is about 66.00% and low productivity is about 33.33%. The productivity of partnership Broiler farming activities were strongly influenced by the number of Broiler hens, farmer experience and labor with the correlation coeffisient respected are 0.776 ; 0.787 and 0.791. The production input of land and extension have significant role on productivity with correlation coefficient respected are 0.406 and 0.422. The conlusion of this study are the number of broiler hens, farmer experience and labor have a strong relation with the productivity of partnership broiler farming activities. The production input of land and extension have less relation with the productivity of partnership broiler farming activities